Preservation of the Optic Radiations based on comparative analysis of Diffusion Tensor Imaging Tractography and Anatomical dissection - Roland eNooij; Eelco eHoving; Arjen evan Hulzen; Frans W. Cornelissen; Remco eRenken (Frontiers in Neuroanatomy, 2015)
Background Visualization of the precise course of the visual pathways is relevant to prevent damage that may inflict visual field deficits during neurosurgical resections. In particular the optic radiations (OR) are susceptible to such damage during neurosurgery. Cortical pathways can be mapped in vivo, by using Diffusion Tensor Imaging (DTI). Visualization of these pathways would be potentially helpful to prevent neurosurgical visual morbidity. In this study an anatomical dissection of the visual pathways was compared to DTI fiber tractography (DTI-FT) data of four human brains. The feasibility of a definition of a Safety Zone is investigated.Methods Four adult brains were dissected using Klingler’s fiber dissection method, which allowed preparation of the OR. Measurements before and after dissection were used to establish distances from the cortex to the OR. DTI-scans were also obtained from these brains to determine the same distances.Results Measurements from specific landmark points on the cortex to the lateral border of the OR were performed in four brains. Analysis through DTI tractography corresponded with the dissection results. Based on the combined results of both dissection and DTI-FT, we defined a quantitative surgical Safety Zone with respect to various anatomical landmarks (in particular the ventricle system)Conclusion We conclude that there is a good correlation between the visualizations of the optic pathways based on dissection and DTI. Furthermore, we conclude that defining a neurosurgical Safety Zone which could preserve the integrity of the OR during surgery, based on the combination of DTI-FT images and dissection is feasible.